THE ROLE OF FEMALE PEACEKEEPERS FOR DEFENSE AND SECURITY PERSPECTIVE IN THE EUROPEAN UNION - Deliah Nur Satarida Yusardi; Henny Saptatia Drajati Nugrahani (International Conference on Social and Islamic Studies, 2021)
The European Union has a border area that includes the largest archipelago. As a region that can represent political, economic, sociocultural, defense, and security aspects, it has a strategic role as the main gate in a country. This study aimed to analyze the role of women (Female Peacekeepers) in defense and security perspectives in the European Union. With the use of qualitative research method using literature studies with secondary data shows the research results that: what has succeeded in constructing an effective gender in Europe can treat women in an amiable manner by issuing policies which can also uphold the level of gender equality in defense and security in the European Union, and also understanding of the role of women in defense and security can be seen from the changes in policies issued to protect women over time to adjust to the current situation